2014
DOI: 10.1021/ml500108s
|View full text |Cite
|
Sign up to set email alerts
|

Azapropellanes with Anti-Influenza A Virus Activity

Abstract: The synthesis of several [4,4,3], [4,3,3], and [3,3,3]azapropellanes is reported. Several of the novel amines displayed low-micromolar activities against an amantadine-resistant H1N1 strain, but they did not show activity against an amantadine-sensitive H3N2 strain. None of the tested compounds inhibit the influenza A/M2 proton channel function. Most of the compounds did not show cytotoxicity for MDCK cells. KEYWORDS: Amantadine, influenza, M2 channel, hemagglutinin, propellane H uman influenza A virus, a memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…According to the reported SAR data and the size of the M2 channel, drug activity is thus dependent on the size of the hydrophobic moiety and the length of the linker that connects the moiety with the amine. This conclusion is continuously confirmed by the recently reported active amines …”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…According to the reported SAR data and the size of the M2 channel, drug activity is thus dependent on the size of the hydrophobic moiety and the length of the linker that connects the moiety with the amine. This conclusion is continuously confirmed by the recently reported active amines …”
Section: Resultssupporting
confidence: 85%
“…This result can be explained by the size of the scaffold, as it has a perpendicular dimension of 4.0 Å and a horizontal length of 7.1 Å, which allows the molecule to fit in the channel in the perpendicular direction. For comparison, azapropellane amine 39 did not inhibit the A/M2 channel well, despite the fact that moderate activity against H1N1 was reported . Azapropellane amine 39 has respective dimensions of 4.9 and 5.8 Å in the horizontal and perpendicular directions, and the size of both sides are longer than 4.2 Å (the radius of M2 channel) (Figure ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on the chemical resemblance, we deemed interesting to assess if our 4,6-diamino-1,2-dihydrotriazines (1, 14 and 16) were also able to inhibit the A/ M2 proton channel expressed in Xenopus oocytes using the TEVC assay. At 100 mM, neither of the three compounds significantly inhibited the wild type or S31N mutant M2 channel [38], thus excluding M2 inhibition as the antiviral mechanism of action in virus-infected MDCK cells (data not shown).…”
Section: Analysis Of the Data Inmentioning
confidence: 95%
“…In this study, we have also revised the configuration of our earlier reported molecules containing allyl groups and oxa-bowl/propellane hybrids. Since non-flattened molecules are implicated in biological systems, our results would be useful in drug design [42]. …”
Section: Resultsmentioning
confidence: 99%